The Effect of Financial Performance and Accounting Profit on Share Return With Inflation As a Moderation Variable - HARDIANTO, Ade Manggala; RAMA, Radian Sri; DARMAYANTI, Novi; SUHARDIYAH, Martha; PANJINATA, Awan (PT Keberlanjutan Strategis Indonesia, 2024)
The fundamental principles of justice and legal certainty are integral components of the rule of law concerning protecting individual rights, specifically in taxation. The enactment of Minister of Finance (MoF) Regulation Number 79 of 2023 is a responsive measure to the demands for adaptive tax regulations due to the evolution of laws. Therefore, this research aimed to analyze MoF Regulation Number 79 of 2023 using qualitative methods to explore and understand the meaning of taxpayers' perspectives relating to assessment procedures in regulation and practice to provide in-depth guidance on assessment in taxation. MoF Regulation 79 of 2023 is necessary for tax system compliance, justice, and legal certainty, serving as a multi-faceted juridical, philosophical, and sociological foundation. The results show that the regulation adheres to legal principles, influencing taxation practices regarding tangible and intangible assets, income tax, Value Added Tax (VAT), and sale agreements. This research contributes to analyzing perceptions of legal certainty and fairness in Tax Policy and the importance of balancing the use of tax regulations for external purposes with internal values and principles of tax justice in practice, which will impact the process of making other tax policies more effective and equitable, ultimately contributing to the promotion of social justice, economic development, and good governance. Moreover, future research can analyze the latest regulations issued as a theoretical and practical foundation for taxpayers, aid in setting valuation standards, and ensure compliance with the changing law for the professional practice of tax experts and accountants.